Where are the large trees? A census of Sierra Nevada large trees to determine their frequency and spatial distribution across three large landscapes - Kane, Van R.; Bartl-Geller, Bryce N.; Cova, Gina R.; Chamberlain, Caden P.; van Wagtendonk, Liz; North, Malcolm P. (Forest ecology and management, 2023)
•Used aerial lidar to census large trees across 3 Sierra Nevada landscapes (396 K ha).•Identified > 8 M trees ≥ 76.2 cm (≥30″) DBH & >2.7 M trees ≥ 101.6 cm DBH (≥40″).•Large tree distribution is aggregated in spatially complex patterns of patches.•Most large trees are in stands with high canopy cover suggesting high densities.•Treatments likely needed to improve large tree resilience to drought & wildfire. Large trees (≥76.2 cm/≥30″ DBH) and especially very large trees (≥101.6 cm/≥40″ DBH) are key structures of Sierra Nevada forests for their ecological function, habitat, and carbon storage. Many of these trees have been lost to historic harvest and more recently to drought and wildfires. Understanding the current frequency and distribution of these large trees is essential to understanding their ecological contribution and management needs. We used airborne lidar to census large trees across three Sierra Nevada landscapes (cumulatively 396 K ha) in lower (dominated by ponderosa pine and mixed conifer) and upper (dominated by red fir) montane forest zones. We used data from a network of Forest Inventory and Analysis (FIA) plots to interpret our lidar-based results for large tree frequency, species, and ages. The lidar data identified > 8 M large and > 2.7 M very large trees, and their mean densities were similar to those from FIA data. Large portions of our study areas had either no or low densities (<20) of large trees per hectare. We found that large and very large tree concentrations were spatially aggregated with most in denser patches containing 20 to 50 + large trees per hectare. Depending on the study area, these often sizable (>1000 ha) patches of dense large trees can cover 20% to 40% of the landscape. (Patches of denser very large trees cover less of the landscape, typically 5% to 10%). However, these large patches are rarely simple blocks. Instead, they typically form complex amorphous matrices interspersed with patches of forests containing shorter trees or non-forest cover. Crucially, almost all large trees were in stands with high canopy cover, suggesting horizontal fuel continuity and low resilience to future wildfires. For lower montane large trees, canopy cover versus large tree density showed almost a unimodal response with canopy cover of 60% to 80% for locations with > 20 large trees per ha. For upper montane large trees, canopy cover versus large tree density showed a more linear relationship for all three study areas. High levels of canopy cover, especially for lower montane forests, suggest settings in which infilling following decades of fire suppression have created overly dense stands with lower resilience to drought and wildfire. Other studies have documented substantial recent losses of these large trees to both factors. The high canopy cover within which almost all large trees exist emphasizes the need for treatment almost everywhere that large trees are present for lower montane forests. This likely will require treatments both within the stands that contain large trees and across the landscapes in which they are found.